2019
DOI: 10.1002/hed.25892
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care and treatment outcomes for local recurrence of NPC after definite IMRT—A study by the HKNPCSG

Abstract: Background This study evaluates the contemporary care for patients with locally recurrent nasopharyngeal carcinoma after failure of the primary course of intensity modulated radiotherapy. Methods Eligible patients were identified through the Hong Kong Cancer Registry database. Patterns of care and treatment outcomes were analyzed. Results Two hundred seventy‐two patients with locally recurrent tumors were identified. Of them, 30.9% received surgery, whereas 35.7% received re‐irradiation (re‐RT). The 5‐year ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…Fatal complications were developed in 17 patients [carotid blowout syndrome (10), brain abscess (3), temporal lobe necrosis (1), dysphagia with aspiration pneumonia (1) and secondary malignancy (2)]. Other severe radiotherapy complications can be found in our recent published patterns of care study …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatal complications were developed in 17 patients [carotid blowout syndrome (10), brain abscess (3), temporal lobe necrosis (1), dysphagia with aspiration pneumonia (1) and secondary malignancy (2)]. Other severe radiotherapy complications can be found in our recent published patterns of care study …”
Section: Resultsmentioning
confidence: 99%
“…We recently reported a territory‐wide study on the patterns of care and treatment outcomes of locally recurrent NPC that were initially treated with intensity modulated radiotherapy (IMRT) in Hong Kong public hospitals from 2001 to 2010 . Ninety‐seven patients were offered re‐irradiation as salvage and they were managed by various radiation doses and techniques according to attending physicians' discretion.…”
Section: Introductionmentioning
confidence: 99%
“…The management strategy outlined above is the most commonly adopted practice in Hong Kong, as shown in a recent Patterns of Care study reported by the HKNPCSG [110]. The study included 272 locally recurrent non-metastatic NPC patients who were treated with a primary course of IMRT: their rT stage distribution was 30.5%, 9.6%, 25.4% and 34.6% for rT1, rT2, rT3 and rT4, respectively.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…Although excellent local control has been achieved with the wide use of intensitymodulated radiation therapy (IMRT), local recurrence remains an important cause of treatment failure in approximately 10% of advanced NPC [4][5][6]. What's worse, for patients with locally recurrent NPC, the salvage treatment options are limited and the prognosis is miserable, with 5-year overall survival ranging from 28-60% in patients with rT3-T4 disease [6][7][8].…”
Section: Introductionmentioning
confidence: 99%